Inhibition of Bilimbi Leaf Extract (Averrhoa bilimbi Linn.) Against the Growth of Candida albicans ATCC 10231 - Muhammad Asril; Riska Marlin (Biota, 2022)
Candida albicans ATCC 10231 is a microflora in the female genital tract that can cause candidiasis/vaginal discharge due to systemic disorders and long-term use of antibiotics. Natural treatment without side effects can use bilimbi leaves (Averrhoa bilimbi Linn.). This plant contains flavonoids, alkaloids, saponins, and tannins which can inhibit C. albicans ATCC 10231. This study aimed to determine the potential of bilimbi leaf extract in inhibiting the growth of C. albicans ATCC 10231. The maceration method using ethanol as a solvent was used to obtain the extract of bilimbi leaves. The antifungal ability of the extract was tested using the well diffusion method. The extraction yield was 7.69% and was able to inhibit C. albicans ATCC 10231 at a concentration of 80% and 100% with an antimicrobial index of 0.66 and 0.95, respectively, with weak and moderate inhibition categories. These results are new information about using bilimbi leaves to inhibit the growth of C. albicans ATCC 10231 so that the public can use it as an alternative treatment for vaginal discharge.